Escaping the corner of death? An eye-tracking study of reading direction influence on attention and memory. Issue 1 (9th January 2017) - Hernandez, Monica D.; Wang, Yong; Sheng, Hong; Kalliny, Morris; Minor, Michael
Abstract : Purpose: The authors aim to examine the effect of location-driven logo placement on attention and memory on the web addressing differences between individuals that read unidirectionally (left-to-right [LTR]) versus bidirectionally (both right-to-left and LTR). Design/methodology/approach: Using an eye-tracking approach combined with traditional verbal measures, the authors compared attention and memory measures from a sample composed of bidirectional (Arab/English) readers and unidirectional readers. Findings: The findings reveal that unidirectional and bidirectional readers differ in attention patterns. Compared to bidirectional readers, unidirectional readers pay less attention to the logo on the bottom right corner of the webpage based on verbal measures. The eye-tracking data of the two groups further identify differences based on total hits and duration time. Unidirectional LTR readers demonstrate higher fluency in feature-based attention whereas bidirectional readers show higher fluency in spatial attention. Originality/value: The authors expand on scarce research on reading direction bias effect on location-driven stimuli placement in online settings. They contribute to the understanding of the differences between unidirectional and bidirectional readers in their cognitive responses (attention and memory) to organization of marketing stimuli.